The Prevalence of Occult Omental Metastases in Patients with Epithelial Ovarian Cancer - Hariyono Winarto; Ken Indra (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: Studies regarding omentectomy on epithelialovarian cancer are scarce with conflicting results; this study isaimed to investigate the prevalence of occult metastases inpatients with epithelial ovarian cancer of the omentum.Methods: A cross-sectional study design was used by evaluating themedical records of surgically staged ovarian cancer patients in Dr.Cipto Mangunkusumo Hospital, Jakarta, Indonesia during the periodof January 2009 to December 2015.Results: A total of 51 subjects were involved in this study. One(2%) of 51 subjects was found to have occult metastases in theomentum. The prevalence of metastases of early stage epithelialovarian cancer in 2009-2015 is 33.3% (17 out of 51 subjects),whereas the omental involvement is found only in 2% subjects(1 out of 51).Conclusion: The prevalence of occult metastases of early stageepithelial ovarian cancer in Dr. Cipto Mangunkusumo Hospital,Jakarta, Indonesia, from 2009-2015 in 2% (1/51 subjects).[Indones J Obstet Gynecol 2018; 6-2: 119-122]Keywords: cancer, epithelial, metastases, omentum, ovarian cancer,ovary, prevalence